Encyrtid Parasitoids of Soft Scale Insects: Biology, Behavior, and Their Use in Biological Control - Kapranas, Apostolos; Tena, Alejandro (2017)
Parasitoids of the hymenopterous family Encyrtidae are one of the most important groups of natural enemies of soft scale insects and have been used extensively in biological control. We summarize existing knowledge of the biology, ecology, and behavior of these parasitoids and how it relates to biological control. Soft scale stage/size and phenology are important determinants of host range and host utilization, which are key aspects in understanding how control by these parasitoids is exerted. Furthermore, the nutritional ecology of encyrtids and their physiological interactions with their hosts affect soft scale insect population dynamics. Lastly, the interactions among encyrtids, heteronomous parasitoids, and ants shape parasitoid species complexes and consequently have a direct impact on the biological control of soft scale insects.